Effect of H2O2 concentrations on copper removal using the modified hydrothermal biochar. (May 2016) - Zuo, XiaoJun; Liu, Zhengang; Chen, MinDong
Highlights: Sorption behaviors of the modified biochar were varying under different H2 O2 levels. Sorption property of the modified HLG by 20% H2 O2 (mHLG2) was the most desirable. H2 O2 modification availably advanced sorption capacity of hydrothermal biochars. The functional groups changed non-uniformly with the increase of H2 O2 levels. Carboxylic group had a significant relationship with H2 O2 modification. Abstract: This study investigated effect of H2 O2 concentrations on copper removal using H2 O2 modified hydrothermal carbonization Cymbopogon schoenanthus L. Spreng (HLG). Sorption behaviors of Cu (II) on the modified HLG by 20% H2 O2 (mHLG2) could be the most desirable. Based on Langmuir isotherm, the maximum amount of Cu (II) uptake was in the sequence of mHLG2 (53.8 mg g −1 ) > mHLG1 (44.2 mg g −1 ) > mHLG3 (42.0 mg g −1 ) > mHLG0 (35.8 mg g −1 ), which was higher than the results from majority of previous studies, suggesting that H2 O2 modification advanced sorption capacity of hydrothermal biochars evidently. Effect mechanisms exploration indicated that the difference of Cu (II) removal by biochars before and after the modification was mainly related to functional groups. Carboxylic group was responsible for the best sorption property of Cu (II) by mHLG2, which was attributed to its significant relationships with H2 O2 modification and Cu (II) removal.